PENGARUH KREDIT TERHADAP PENDAPATAN PADA PT. BANK BENGKULU - Rinto Noviantoro; Iwin Juita (UNIVED Press, 2019)
This study aims to analyze the effect of consumption credit, working capital credit, and investment credit on revenue at PT. Bank Bengkulu. The data used are secondary data derived from the annual financial statements of PT. Bank Bengkulu from 2010 to 2017. Data testing methods used is multiple linear regression analysis, correlation analysis, determination coefficient (R2), by testing the statistical hypothesis t (t test) and F statistical test (F test). The results of the study using multiple linear regression test obtained the regression equation Y = 470287,976 - 0.035 X1 - 20,430 X2 + 46,218 X3. That is, if the consumption credit, working capital credit, and investment credit is worth 0, then the revenue is Rp. 470,287. If there is a decrease in consumption credit of Rp. 1, then the value of revenue decreases by Rp. -0,035, - if the working capital loan decreases by Rp. 1, then the revenue will decrease by Rp. 0 20,430, - and if the investment credit increases by Rp. 1, - then the revenue will increase by Rp. 46,218. The test results of the coefficient of determination (R2) indicate that the credit given has an effect of 20.5% on revenue. While 79.5% is influenced by other factors not examined. The results of partial hypothesis testing (t test) state that consumption credit has a negative and not significant effect on revenue with a significant value of 0.820 and t count of -0.244<2.446 t table. The testing results of working capital loans show a negative results and not significant effect on revenue with a significance value of 0.379 and t count of -0.988<2.446 t table. The results of the investment credit test show that the results have a positive and not significant effect on revenue with a significance value of 0.371 and a value of t count -1.008<2.446 t table. While the simultaneous test results show that consumption credit, working capital credit, and investment credit have no significant effect on revenue with a significance level of 0.796 and a calculated F count of 0.344 < F table of 5.786.